The Impact of Health Literacy on Surgical Outcomes Following Radical Cystectomy - Scarpato, Kristen R. (J Health Commun, 2016)
Health literacy is the ability to obtain, comprehend and act on medical information and is an independent predictor of health outcomes in patients with chronic health conditions. However, there is little reported regarding the potential association of health literacy and surgical outcomes. We hypothesized that patient complications after radical cystectomy (RC) are associated with health literacy. In a sample of 368 patients, we found that higher health literacy scores (as determined by the Brief Health Literacy Screen) are associated with decreased odds of developing minor complications (OR=0.90, 95% CI: 0.83,0.97). Health literacy should be considered when caring for patients undergoing radical cystectomy and serve as a potential indicator of the need for additional resources to improve post-operative outcomes.